Does Flow Experience Really Matter among Hotel Employees in Sarawak? - Kasa, Mark; Hassan, Zaiton; Yatim, Azizan (International Journal of Engineering and Technology, 2018)
Studies on flow in the Malaysian hotel context are still very limited even though it is an important psychological phenomenon toward developing human resources. This present study aims to investigate the role of flow experience as a mediator between the causes of burnout and its outcomes (turnover intention and work-family conflict) among the hotel employees in Sarawak, Malaysia. In the hotel industry, which has a highly demanding working environment, employee burnout would eventually lead to turnover intention and work-family conflict (WFC). To minimize these causes and outcomes, flow is hypothesized as a possible mediator in this study. The data were collected from 210 full time hotel employees, selected by random sampling method, and analyzed using SPSS version 20 and PROCESS version 2.11. The findings revealed that flow played a direct and indirect significant role between the causes of burnout and its outcomes. The findings suggest flow to be an important approach in alleviating the effects of burnout â€“ turnover intention and work-family conflict.Â Â